Archaeoseismology in the Inka Sacred Valley and in the Cuzco region, an interdisciplinary approach for past seismic impacts characterization on Cultural Heritage as a new marker for paleoevents? - Combey, Andy (2019)
Trabajo presentado en el 8th International Symposium on Andean Geodynamics (ISAG), realizado en Quito-Ecuador, del 24-26 setiembre, 2019. Evento organizado por el Instituto Geofísico, Escuela Politécnica Nacional (IG-EPN) del Ecuador, y el French Institut de Recherche pour le Développement (IRD).